2012
DOI: 10.1017/jmech.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Flow of a Second Grade Fluid over a Stretching Surface with Newtonian Heating

Abstract: ABSTRACTThis article describes the boundary layer flow and heat transfer in a second grade fluid over a stretching sheet. Heat transfer analysis is carried out in the presence of a Newtonian heating. The partial differential systems have been transformed into the ordinary differential systems by appropriate relations. Homotopy analysis method (HAM) is used for the solutions. Graphical and tabulated results are presented to see the significance of influential parameters on the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Recently, Newtonian heating effects have been utilised by different researchers because of their practical applications such as to design heat exchanger, conjugate heat transfer around fins, and also in convection flows setup where bounding surfaces absorb heat by solar radiations. Hayat et al [18] examined boundary layer flow of second-grade fluid with Newtonian heating. Three-dimensional magnetohydrodynamic flow of couple stress fluid with Newtonian heating is investigated by Ramzan et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Newtonian heating effects have been utilised by different researchers because of their practical applications such as to design heat exchanger, conjugate heat transfer around fins, and also in convection flows setup where bounding surfaces absorb heat by solar radiations. Hayat et al [18] examined boundary layer flow of second-grade fluid with Newtonian heating. Three-dimensional magnetohydrodynamic flow of couple stress fluid with Newtonian heating is investigated by Ramzan et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the increase of conjugate parameter for the Newtonian heating enhanced both surface temperature and the heat transfer coefficient. Other related papers included from the works by Kasim et al [12], Hayat et al [13], Sarif et al [14] and recently by Hussanan et al [15] who investigated the Soret effects on unsteady magnetohydrodynamic mixed convection heat and mass transfer flow in a porous medium. Therefore, the aim of this study is to investigate the buoyancy effect on stagnation point flow over a stretching vertical surface with Newtonian heating.…”
Section: Introductionmentioning
confidence: 99%
“…A few recent articles have discussed the flow of second grade fluid in literature [1][2][3][4][5][6]. Certain progress and related work on unsteady flow of second grade fluid have been discussed by Gul et al [7].…”
Section: Introductionmentioning
confidence: 99%